Dynamics of the extended and intermediate range order in model polymer electrolyte poly(ethylene oxide) and lithium bis(trifluoromethanesulfonyl)imide - Falus, Peter; Faraone, Antonio; Förster, Stephan; Hong, Kunlun; Ohl, Michael (Frontiers in Soft Matter, 2023)
The dynamics of lithium ions and polymer chains were investigated at the molecular scale in the model polymer electrolyte Poly (ethylene oxide) (PEO)/Lithium bis(trifluoromethanesulfonyl)imide as a function of temperature. This system is known to present an intermediate range order from the arrangement of neighboring chain segments as well as an extended range order of cylindrically arranged chains. The collective dynamics of the systems at lengthscales matching these structural features was measured using Neutron Spin Echo spectroscopy, gaining insights into their lifetime. Moreover, using isotope substitution techniques the dynamics of the lithium ions with respect to the other atoms was probed. The obtained results are compared with the conductivity and the lithium self-diffusion coefficient measured by NMR to gain experimental insight on the molecular processes triggering lithium transport.